2017
DOI: 10.1080/09168451.2017.1373591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of difructose anhydride III, raffinose, and fructooligosaccharides on energy intake, gut hormones, and cecal fermentation in rats fed a high-fat and high-sucrose diet

Abstract: We investigated the effects of dietary supplementation of difructose anhydride III (DFA III), raffinose (Raf), and fructooligosaccharides (FOS) on diet-induced obesity development. Male rats were fed normal or high-fat and high-sucrose (HFS) diet, with or without supplementing (3%) DFA III, Raf, or FOS, for 8 or 5 weeks. Supplementing DFA III to the HFS diet decreased energy intake compared to the non-supplemented HFS diet. Accordingly, body weight gain and fat accumulation reduced in DFA III-fed rats. Cecal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition to the oligosaccharides described above, some NDOs have also been reported to have weight loss activity. Raffinose-oligosaccharides (RFOs) are nondigestible oligosaccharides composed of galactose, glucose, and fructose, that are found in a variety of vegetables, including cabbage, broccoli, beans, and ginger. , RFOs are reported to have some weight loss effects and to optimize intestinal ecology activity …”
Section: Ndos With Antiobesity Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the oligosaccharides described above, some NDOs have also been reported to have weight loss activity. Raffinose-oligosaccharides (RFOs) are nondigestible oligosaccharides composed of galactose, glucose, and fructose, that are found in a variety of vegetables, including cabbage, broccoli, beans, and ginger. , RFOs are reported to have some weight loss effects and to optimize intestinal ecology activity …”
Section: Ndos With Antiobesity Activitymentioning
confidence: 99%
“…Raffinose-oligosaccharides (RFOs) are nondigestible oligosaccharides composed of galactose, glucose, and fructose, that are found in a variety of vegetables, including cabbage, broccoli, beans, and ginger. 91,92 RFOs are reported to have some weight loss effects and to optimize intestinal ecology activity. 93 Many marine polysaccharides have been shown to have metabolic benefits.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…A decrease in body weight was observed in the rats fed with DFAIII supplementation as compared to those fed with DFAIII-free diets. As mentioned before, an increase in acetic acid level was observed in the gut that served as a potent stimulator to secrete anorexic gut hormones such as glucagon-like peptide-1 and peptide YY [28]. It was recently revealed that acetic acid reduces appetite via direct influence on hypothalamus in the brain without induction of these gut hormones [29].…”
Section: Discussionmentioning
confidence: 87%
“…Opposing the HF group (67.65 g/100 g) that had the highest body fat, the feeding of FOS-RMD mixture could effectively ( p < 0.05) lower the total body fat in HF1X (23.76 g/100 g) and HF2X (22.72 g/100 g) diets by −15.5% and −19.2%, respectively. Other authors have also revealed the potential of FOS and RMD in hurdling intestinal fat absorption and mitigating the fat tissue accumulation even though these dietary fibers were administered separately [ 16 ]. In this study, an administration of either 2% or 5% of FOS-RMD mixture has contributed to a reduction of fat accumulation in the rats fed different high fat diets.…”
Section: Resultsmentioning
confidence: 99%